Relative Contributions of Selected Teachers’ Variables and Students’ Attitudes Toward Academic Achievement in Biology Among Senior Secondary School Students in Ondo State, Nigeria. - Gbore, L.O. (Mediterranean Journal of Social Sciences, 2013)
This study investigated the relative contributions of selected teachers’ variables and students’ attitude towards academicachievement in biology among senior secondary schools in Ondo State, Nigeria. It involved descriptive survey research andex-post facto research designs. The sample, 360 respondents which consists of 180 biology teachers and 180 seniorsecondary school three students were randomly selected from 36 senior secondary schools from the three Senatorial Districtsof Ondo State using stratified random sampling technique. Teachers’ teaching attitudinal scale, Science oriented attitudinalscale and an inventory which requested for data from records on students’ senior secondary school certificate examinationgrades in biology were used for data collection. Data collected for the study were analyzed using correlation matrix andmultiple regression analysis. The results showed that significant relationships existed among the independent variables andstudents’ academic achievement in biology. Also 62.5% of the variance observed in students’ achievement in biology wasexplained by linear combination of the five predictor variables. Students’ attitude was the most potent contributor to theprediction. Teachers’ workload was the least contributor to the prediction. It was recommended that constant workshops andseminars should be made available by government for teachers to attend for the improvement of their teaching skills.Teachers and students were also charged to change their attitudes positively towards the teaching and learning of biology.